2007
DOI: 10.21273/hortsci.42.5.1174
|View full text |Cite
|
Sign up to set email alerts
|

Flowering and Fruiting Patterns of Primocane-fruiting Blackberries

Abstract: The flowering morphology of the erect, thorny, primocane-fruiting blackberry (Rubus L. subgenus Rubus, Watson) cultivars ‘Prime-Jan’ and ‘Prime-Jim’ were studied in 2005 and 2006 in Aurora, OR. Primocanes that were “soft-tipped” in early summer to 1 m were compared with untipped primocanes. In both years, soft-tipped primocanes developed two- to threefold more branches and almost twice the number of flowers as untipped canes. ‘Prime-Jan’ and ‘Prime-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…In contrast, early-season berries on double-tipped canes in 2007 had a higher percentage of drupelets set than late-season berries; percent drupelet set was fairly consistent throughout the 2007 harvest season in treatments that were tipped once at 0.5 m (control ; Table 3). This occurrence of more ovules per flower early in the season is perhaps because the first, and often largest, flowers develop on the apices of the primary and secondary floral axes, as described in Thompson et al (2007). This has also been reported by Strik et al (1996) in other blackberry genotypes.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In contrast, early-season berries on double-tipped canes in 2007 had a higher percentage of drupelets set than late-season berries; percent drupelet set was fairly consistent throughout the 2007 harvest season in treatments that were tipped once at 0.5 m (control ; Table 3). This occurrence of more ovules per flower early in the season is perhaps because the first, and often largest, flowers develop on the apices of the primary and secondary floral axes, as described in Thompson et al (2007). This has also been reported by Strik et al (1996) in other blackberry genotypes.…”
Section: Resultssupporting
confidence: 64%
“…Soft-tipped branches in double-tipped canes typically developed two to three inflorescences (0.10 to 0.15 m in length), whereas untipped branches in all other treatments ended in a single inflorescence. Other studies on 'Prime-Jan' have showed that soft-tipping at 1 m removed apical dominance and promoted branching (Strik et al, 2008;Thompson et al, 2007). The additional pruning of soft-tipped branches in the double-tipped treatment likely had a similar effect on promoting inflorescence development.…”
Section: Resultsmentioning
confidence: 81%
“…2005;Clark 2008), develop PSs that possess a terminal panicle and two flowering side branches of the stem and hence can be classified as the complex type of PS (according to the definition of this study). If the tip is cut in spring to prevent development of the terminal panicle of the stem, two additional flowering / fruiting branches are formed resulting in average higher yields (Thompson & al. 2007;Strik 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Soft-tipping of canes is necessary to manage primocane growth and to increase yield; however, tipping height can affect cane architecture and season. In addition, double-tipping, where primocane branches are soft-tipped also, shows great promise for increasing production (Thompson and Strik, 2007).…”
Section: Off-season Productionmentioning
confidence: 99%